Utility of Flow Cytometry in Diagnosing Hematologic Malignancy in Tonsillar Tissue. (August 2017) - Aisagbonhi, Omonigho; DeLelys, Michelle; Hartford, Nicole; Preffer, Frederic; Ly, Amy
Objective . Tonsil surgical biopsy or excision is a very common procedure. However, there exist no consensus guidelines for the pathologic handling of tonsil specimens; gross and/or microscopic evaluation may be used. Diagnosis of tonsillar hematologic malignancy requires histology, immunohistochemistry and/or flow cytometry. Data regarding the utility of flow cytometry in tonsillar tissues are limited. We assessed our experience with flow cytometry for tonsil diagnosis with regard to accuracy and use patterns at a tertiary academic medical center. Methods . We retrospectively analyzed all surgically biopsied or excised tonsil specimens that underwent flow cytometry evaluation from August 2011 to March 2014. Patient clinical information, intraoperative frozen section, histology, immunohistochemistry, and flow cytometry diagnoses were recorded. Results . The study included 154 tonsil specimens from 89 females and 65 males. Patients averaged 27.4 years old (range 2-87 years); 73 were pediatric. Both histology and flow cytometry were benign for 148 patients (96.1%). Hematolymphoid malignancy was diagnosed in 6 adults by histology/immunohistochemistry: diffuse large B-cell lymphoma (2), small B-cell lymphoma (2), concomitant follicular lymphoma and histiocytic sarcoma (1), and extraosseous plasmacytoma (1). Flow cytometry identified abnormal populations in 5 of 6 cases, and detected clonal populations in 2 reactive follicular hyperplasia cases. Conclusion . Tonsillar hematolymphoid malignancy is uncommon, and flow cytometry was less accurate than histology/immunohistochemistry for its diagnosis. Despite the rarity of tonsillar lymphoma in children, nearly half of study patients were pediatric. Intraoperative frozen section diagnosis showed excellent sensitivity for malignancy, and could be used to effectively triage cases for flow cytometry evaluation.